2016
DOI: 10.3126/jnarc.v2i0.16118
|View full text |Cite
|
Sign up to set email alerts
|

Is Investment in Maize Research Balanced and Justified? An Empirical Study

Abstract: The objective of this study was to investigate whether the investment in maize research was adequate and balanced in Nepalese context. Resource use in maize research was empirically studied with standard congruency analysis by using Full Time Equivalent (FTE) of researchers as a proxy measure of investment. The number of researchers involved in maize was 61 but it was only 21.25 on FTE basis, indicating that full time researchers were very few as compared to the cultivated area of maize in the country. Statist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Rice productivity is low in Nepal as compared to global average productivity of 4.0 mt ha -1 due to poor investment in research, technological development (Gauchan and Pandey 2011), mismatch in resource allocation (Shrestha and Gairhe 2016) and inadequate inputs and management practices , Timsina et al 2012. In support of these ideas, several studies reported that farmers have been applying lower fertilizer rates than recommended which caused higher yield gaps .…”
Section: Discussionmentioning
confidence: 99%
“…Rice productivity is low in Nepal as compared to global average productivity of 4.0 mt ha -1 due to poor investment in research, technological development (Gauchan and Pandey 2011), mismatch in resource allocation (Shrestha and Gairhe 2016) and inadequate inputs and management practices , Timsina et al 2012. In support of these ideas, several studies reported that farmers have been applying lower fertilizer rates than recommended which caused higher yield gaps .…”
Section: Discussionmentioning
confidence: 99%
“…ough agricultural imports have increased drastically, domestic production is also increasing slowly. It is thought that plant breeding played a significant role in [20]. In Nepal, local germplasm are barely used in research as mostly foreign genetic stocks are preferred.…”
Section: History Of Plant Breeding In Nepalmentioning
confidence: 99%
“…During the HMRP period of 10 years, 174 CBSP groups and cooperatives were formed and seed production volume increased from 14 tons in 2000 to 830 tons in 2010 ( HMRP-CIMMYT, 2010 ). HMRP, funded by the Swiss Government, resulted in higher investment into maize research over the period ( Shrestha and Gairhe, 2016 ).…”
Section: Introductionmentioning
confidence: 99%